MODEL KOMUNIKASI KOMUNITAS TULI di SLB NEGERI JEMBER - Mohammad Syarif Hidayat (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2021)
The research aims to describe the communication model of Deaf community in SLB Negeri Jember. The limitation of function of hearing sense system makes an influence on optimalizing human communication tool as verbal language in line with negative implication to the development of intelectuality, emotion, personality, social life, and another aspects. The difficulty to articulate their feeling, thought, and experience is caused by minimum vocabs they acquired. So, it makes them simplifying the utterances, actually with various different meaning for normal people (red: orally cultured-people). The fatal mistakes in understanding the meaning of utterances are able to make a wrong perception on the intention and the goal of using them. The mistakes in positioning communication elements in the society culture are going to make the communication failure in result, moreover, to arise conflict and violance. This research used a case study. Data were collected using documentation method and interviews. The data analysis is done through descriptive data and content analysis.